THU0087 Microrna-1915–3p in serum exosome is associated with disease activity of rheumatoid arthritis in korea. (12th June 2018) - Lim, M.-K.; Song, J.; Kim, S.A.; Yoo, J.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease that is characterised by severe tissue damage and chronic synovial inflammation. 1 Using analysis of gene polymorphism, biochemical assays, and proteomics approaches, several promising biomarkers for treatment response have been proposed, including red blood cell (RBC) MTX polyglutamate levels, as well as serum levels of proteins such as cytokines, growth factors, and autoantibodies. 2 However, these markers need further development and refinement to attain sufficient sensitivity and specificity. Objectives: In this study, we used a miRNAarray approach to identify new miRNA in exosome that are related to disease activity in patients with RA who showed inadequate response to treatment. We also examined the relationship between the levels of expression of the RNAs and various serologic parameters of the patients. Methods: Forty-two RA patients were included in the study. Disease activity was measured using the 28-joint disease activity score with ESR (DAS28-ESR). Patients with RA were stratified according to the following criteria: the clinical remission (CR) group (n=22), DAS28-ESR≤2.6; and the non-CR group (n=20), DAS28-ESR>2.6. By exosome preparation, miRNA array, and Reverse Transcription-qPCR reactions, several miRNAs were as potent markers for disease activity. Results: After data processing for relative quantification of miRNA in exosome between the CR and non-CR groups, we identified 47 miRNAs with a relative fold change (non-CR/CR)>2. The expression levels of 37 miRNAs were found decreased in non-CR group, while 10 miRNAs increased in non-CR group. To validate these results, five miRNAs were selected (hsa-miR-1915–3 p, hsa-miR-4516, has-miR-6511b-5p, hsa-miR-3665, hsa-miR-3613) showing at least 2-fold change between the CR and non-CR groups. Both levels of hsa-miR-1915–3 p and hsa-miR-6511b-5p were significantly increased in CR group; hsa-miR-1915–3 p was 43.75 in the CR group and 24.68 in the non-CR group (p=0.004), and hsa-miR-6511b-5p was 3.02 in the CR group and 2.45 in the non-CR group (p=0.03). Conclusions: hsa-miR-1915–3 p showed promise as additional markers for evaluating disease activity in patients with RA. Prospective investigation of hsa-miR-1915–3 p may facilitate development of new diagnostic tools to assess disease activity and prognosis in RA and other autoimmune diseases. References: [1] Lee DM, Weinblatt ME. Rheumatoid arthritis. Lancet(London, England) England 2001;358:903–11. [2] Halilova KI, Brown EE, Morgan SL, Bridges SL, Hwang MH, Arnett DK, et al. Markers of treatment response to methotrexate in rheumatoid arthritis: Where do we stand?Int J Rheumatol2012;2012. Acknowledgements: NONE Disclosure of Interest: None declared